Strategic Renewal at Finnair Amid Dual Crises: A Case Study on Dynamic Capabilities - Česnulis, Antanas (2025)
Towards the end of 2019, the COVID-19 pandemic, which would later unfold into a global crisis, began to emerge. The subsequent closure of Russian Airspace for Western carriers, including Finnair, led to an unprecedented dual crisis for the national carrier of Finland, dismantling its well-established Europe-Asia business model. As a result, the carrier was put into an accelerated process of strategic renewal, entering an era of intense volatility, strategic uncertainty and survival-driven transformation. While existing literature extensively covers strategic renewal, crisis management, and dynamic capabilities, few studies are exploring how firms strategically adapt during overlapping, prolonged exogenous shocks. There is even less information about how such adaptations unfold in sequence and how firms combine emergent and deliberate strategic actions into long-term strategic repositioning. This thesis addresses the gap by offering a process-oriented, empirically grounded analysis of how Finnair renewed its corporate strategy and capabilities in the face of high levels of uncertainty. To uncover the findings, the thesis employs Event Structure Analysis, utilising 23 causally linked strategic events from 2019 to 2024, distilled from 123 events. This analysis is supported by a thematic analysis of 236 coded actions, as well as complementary quantitative data, including revenue mix and RPK/ASK trends. The results include (1) the identification of five sequential phases of strategic renewal, from crisis reaction to long-term repositioning, (2) discovery of a transition from reactive to proactive strategy, (3) with increasing use of dynamic capabilities (sensing, seizing and reconfiguring), (4) evidence for essential drivers such as stakeholder engagement, partnerships and revenue diversification, and (5) quantitative findings (e.g. surge in cargo revenue) aligning with strategic shifts observed in the Event Structure Analysis and complementary findings. The findings contribute to the strategic management literature by bridging dynamic capabilities theory with an action-based view in a real-life, high-volatility setting. They serve practical insights for firms navigating subsequent disruptions, highlighting the importance of agility, asset leverage, corporate learning, and organisational reconfiguration to achieve successful long-term renewal.